Pengaruh Ukuran Perusahaan, Return on Asset (ROA), leverage, dan umur Listing terhadap Pengungkapan Internet Financial and Sustainability Reporting (IFSR) pada Perusahaan Manufaktur yang Listed di Bursa Efek Indonesia (BEI) tahun 2009-2012 - Lisa Agustina Leonardi; Theresia Purbandari; Dwi Handayani (Fakultas Bisnis, 2014)
Internet Financial and Sustainability Reporting is a presentation of the financial statements and the sustainability of the company through the internet . The company's website is not only used for product marketing media, but also be used to share the important information in the corporate financial statements and sustainability reports. The purpose of this research is to examine the effect of firm size, profitability, leverage, liquidity, ownership of outsiders, and how long the listing progress corporate in BEI toward to IFSR disclosure. The population in this research is the manufacturing companies which is listed on the Indonesian Stock Exchange in 2012. The samples that used in this research were 53 companies that were taken by purposive sampling technique. Sampling criteria, such as: a company that has a website and share the financial statements from 2007 to 2012. The analytical tool that used to test the hypothesis in this research is a panel data regression analysis by using statistical software Eviews 4.1. The results of this research indicate that the firm size, return on assets ( ROA ), leverage, and the listing progress have a positive significant effect toward IFSR disclosure. While the return on equity (ROE), leverage, liquidity, and external ownership have no effect against the IFSR disclosure.